A Review on Violence Against Health Care Professionals in India and Its Impact - Gadapati, Suresh; B R, Shamanna (National Journal of Community Medicine, 2023)
Background: Workplace violence (WPV) is an emerging and contextually relevant public health problem among healthcare professionals (HCPs) globally, including in India. It is now recognized as a significant occupational hazard and an emergency public health problem. This study reviewed to identify the concept and prevalence of WPV, its trend, consequences, impact on healthcare professionals, and preventative measures in the Indian Context. Methods: We searched Pub Med, Google Scholar, Scopus and other source, for the published articles between 2014 and 2022. Results: We included 25 studies in total. Doctors and nurses are victims in Emergency Rooms, Intensive Care Units, and Outpatient departments (OPD). The majority of incidents across all contexts involved verbal violence. Patients and visitors are perpetrators of WPV and has impacts on service. Waiting time, poor communication, infrastructural issues, and negative media coverage are predisposing factors to WPV against HCPs. Conclusion: While WPV showing increased trends, there is a need for a more systemic approach to reducing violence in the workplace that incorporates accountability at various tiers.